A luz como linguagem nas campanhas dos perfumes Chanel e Tom Ford (ModaPalavra e-periódico, 2012)
The article discusses the use of photographic lighting as an element of speech and help in the construction of the visual message of the advertising campaigns of the brands of perfume Chanel and Tom Ford. For this purpose we used the analysis of two campaigns for Chanel No. 5 perfume and two for Tom Ford for men. The campaigns were analyzed under the bias of semiotic plastic Julien Greimas and Jean-Marie Floch and used the concepts of photographic language and visual rhetoric.
Keywords: campaigns of perfume; analysis of image; photographic lighting